USING FORUM THEATRE TO DEVELOP VARIOUS LEVELS OF THINKING SKILLS AMONG MORAL EDUCATION STUDENTS IN SECONDARY SCHOOL (Malaysian Journal of Learning and Instruction, 2020)
Purpose â€“The power of forum theatre in education and various other fields is well known by educators. However, the use of forum theatre in Malaysia, particularly in the field of moral education, is still limited. At the same time, the development of thinking skills is one of the aims of the Malaysian moral education curriculum. Therefore, this study examined the use of forum theatre as a pedagogical tool in developing various levels of thinking skills among moral education students. Method â€“The study adopted a qualitative research design and was underpinned by Bloomâ€™s revised taxonomy as the theoretical and analytical framework. A total of 14 moral education students participated in this study. Data were collected qualitatively using classroom observations, interviews, and journal writing. Thematic analysis was utilized to analyse and present the findings. Findings â€“The findings revealed that various theatrical activities that underpinned the four elements of forum theatre: (i) writing a script, (ii) delivering a dialogue in an anti-model play, (iii) discussion and decision-making in a forum session, and (iv) improvisation in an intervention play, show the development of studentsâ€™ thinking skills at the level of analysing, evaluating and creating. Therefore, this study suggests that forum theatre can be used in moral education pedagogy to enhance higher order thinking skills. Significance â€“ Meaningful instructional pedagogy must inspire thinking skills to foster creativity and innovation among students. This is considered an important skill in 21st century learning. Hence, these findings are beneficial for teachers, lecturers, parents and instructional designers who wish to plan and implement suitable teaching methods such as forum theatre to empower and improve studentsâ€™ thinking skill levels.